Penerapan Metode Technique for Orders Preference by Similarity to Ideal Solution (TOPSIS) dan Rank Order Centroid (ROC) Dalam Pemberian Beasiswa Kartu Indonesia Pintar (KIP) - Ita Arfyanti (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
The provision of KIP scholarships, which are aid scholarships given when a person is still in high school/vocational school, or assistance for high school/vocational high school graduates to continue their education. This assistance is given to students who have good academic potential and have economic limitations. When searching for and determining recipients of scholarship assistance for KIP scholarship recipients by implementing a decision support system using the Technique for Orders Preference by Similarity to Ideal Solution (TOPSIS) method approach where the selection criteria have been determined previously, the criteria are given or weighted using the ROC method ( Rank Order Centroid), so that the election data process will get more optimal results using the TOPSIS method, the results obtained are 0.66061 which is the highest value of all alternative data and in this study shows the data is more shaped to the selection of potential alternatives. get a KIP scholarship with a more accurate weight and ranking process.